WOMEN’S HEALTH IN PRIMARY CARE: PREVENTION AND PROMOTION OF CARE - Dayanna Alves Resende, Tamires; da Silva Santos, Samara; Cristina Cavalcante Lucena, Cybelle; Clara Ribeiro Costa, Maria; Medeiros Borburema, Myllena; Carolina Salustino dos Santos, Maria; Claudino do Nascimento, Nathalia (Health and Society, 2022)
In the sphere of women’s health, practices are based on the National Policy for Integral Attention to Women’s Health, which will guide actions aimed at cervical and breast cancer, reproductive health, prenatal care, childbirth and the puerperium. Qualitative, descriptive and reflective research, built in the year 2022. However, the health team and the public power play a fundamental role in this assistance, as they are able to develop strategies that meet this female population, taking into account their particularities and needs , with the objective of promoting and preventing care.